Necessity of thoracotomy in pulmonary metastasis of osteosarcoma - Gao, Erji; Li, Yang; Zhao, Weigang; Zhao, Tiancheng; Guo, Xiang; He, Weiwei; Wu, Weiming; Zhao, Yonghong; Yang, Yi (Journal of Thoracic Disease, 2019)
Background: With the popularization of minimal invasive surgery, video-assisted thoracoscopic surgery (VATS) is gradually replacing conventional thoracotomy for lung cancer and is even used for osteosarcoma patients with pulmonary metastasis. In this study, we characterized the need for open surgery by comparing computer tomography (CT) diagnosis and postoperative pathology of patients with pulmonary metastases of osteosarcoma. Methods: A retrospective analysis was carried out on patients with underwent surgery for pulmonary metastatic osteosarcoma admitted to our hospital between January 2008 and July 2018. The numbers of pulmonary metastatic nodules suspected by preoperative CT scan were calculated in addition to the number of nodules which were resected and pathologically confirmed to be metastatic during surgery. The Spearman correlation coefficient between the number of nodules on preoperative CT scan and the number of lesions pathologically confirmed was calculated. Results: In total, 69 patients undergoing 96 thoracotomy operations were included in this study. The median interval between preoperative CT examination and operation was 7 days (range, 1–44 days). The median number of the suspected nodules on preoperative CT and the pathologically positive metastases resected during operation were 1 and 3, respectively. Remarkably, 36 (37.5%) thoracotomies revealed that more metastatic nodules were detected during thoracotomy than preoperative CT scans. Conclusions: Preoperative CT examination omits a few small pulmonary metastases of osteosarcoma and there is rare progress in recent years. Therefore, we recommend that patients with pulmonary metastases of undergo thoracotomy to locate and resect all metastases as much as possible through intraoperative direct palpation.